Effect of microfines content on mortar compressive strength within the West Coast region of Sabah - Norliza Rima Norbidin, 1982-, author; Abdullah Zawawi Awang, 1964-, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2019